Implementasi Manajemen Berbasis Kinerja dalam Pengelolaan Guru dan Tenaga Kependidikan di SMP Muhammadiyah 1 Simpon Surakarta - Wahid Ahmad Al-Qodri; Mohamad Ali (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to analyze the implementation of performance-based management in the management of teachers and education personnel (GTK) at SMP Muhammadiyah 1 Simpon Surakarta and examine the supporting and inhibiting factors. This study used a descriptive qualitative approach with field research. Data collection techniques were conducted through observation, interviews, and documentation, with the principal as the primary subject. Data analysis used the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results indicate that the implementation of performance-based management in the management of GTK at SMP Muhammadiyah 1 Simpon Surakarta is carried out through several processes: performance planning, performance implementation, coaching and development, monitoring and evaluation, and follow-up on performance results. Supporting factors for the implementation of performance-based management include a well-organized management system and effective communication between work units. Inhibiting factors include the gap between senior and new teachers, as well as limited mastery of information technology among some senior teachers. This study concludes that performance-based management has been implemented quite effectively, although it still requires strengthening in the aspects of competency development and technology adaptation to improve GTK performance sustainably.